Elderly Perceptions about Covid-19 Vaccination - Ridlwan Kamaluddin; Eva Rahayu (Journal of Bionursing, 2023)
Background: The elderly are one of the groups vulnerable to disasters, especially the Covid-19 pandemic. Prevention of Covid-19 in the elderly can be increased through vaccination and health promotion efforts. The achievement of COVID-19 vaccination for the elderly is still in the low category and far from expectations. It is possible that the elderly's perception of the covid vaccination can influence the behavior of the elderly in making decisions to take the Covid-19 vaccine. Aim: To identify the elderly's perception of the covid-19 vaccination. Method: The method used in this research is a quantitative descriptive study.. Sampling was carried out using the total sampling technique Data collected using research instruments in the form of questionnaires developed from the Health Belief Model theory. Results: Based on the perception component of the HMB,majority of all perceptions showed moderate results. A perceived vulnerability level of 77.5%, a perceived seriousness of 70.15%, a perceived benefit of 75%, a perception of self-efficacy 83.8% and a cues to act 78.3%, and the majority of perceptions of barriers that are lacking are 75.8%. Conclusion: The majority of elderly’s perception showed moderate results.